Bargaining and inequality in the labor market - Sydnee Caldwell; Ingrid Haegele; J&#x0308 Heining; о rg (W.E. Upjohn Institute for Employment Research, 2025)
We use novel surveys of firms and workers, linked to administrative employer-employee data, to study the prevalence and importance of individual bargaining in wage determination. We show that simple survey questions accurately elicit firms' bargaining strategies. Using the elicited strategies for 772 German firms, we document that the majority of firms are willing to engage in individual wage bargaining. Labor market factors predict firms' strategies better than firm characteristics. Survey responses from nearly 10,000 full-time workers indicate that most worker-firm interactions begin with the worker rejecting the offer and remaining at the incumbent firm. There is substantial heterogeneity in workers' bargaining behavior, which translates into within-firm wage inequality. Firms that set pay via individual bargaining have a 3 percentage point higher gender wage gap.
Keywords: D83; J31; J41; J53; L21; 330; wage bargaining; employer-employee; Germany; wage inequality; gender wage gap